THE STUDY OF CULTURE IN CULTURAL STUDIES (Conferencea, 2022)
Cultural studies (culturology) was formed as an independent science of culture. It was formed at the intersection of such disciplines as philosophy, history, anthropology, sociology, psychology, ethnology, ethnography, linguistics, art history, semiotics, computer science. All of the phenomena were the basis for the article and researchers discussed about the cultural competence and its usage in the translation